Hearing loss and healthy aging : workshop summary - Lustig, Tracy A.; Olson, Steve, 1956- (National Academies Press, 2014)
"Being able to communicate is a cornerstone of healthy aging. People need to make themselves understood and to understand others to remain cognitively and socially engaged with families, friends, and other individuals. When they are unable to communicate, people with hearing impairments can become socially isolated, and social isolation can be an important driver of morbidity and mortality in older adults. Despite the critical importance of communication, many older adults have hearing loss that interferes with their social interactions and enjoyment of life. People may turn up the volume on their televisions or stereos, miss words in a conversation, go to fewer public places where it is difficult to hear, or worry about missing an alarm or notification. In other cases, hearing loss is much more severe, and people may retreat into a hard-to-reach shell. Yet fewer than one in seven older Americans with hearing loss use hearing aids, despite rapidly advancing technologies and innovative approaches to hearing health care. In addition, there may not be an adequate number of professionals trained to address the growing need for hearing health care for older adults. Further, Medicare does not cover routine hearing exams, hearing aids, or exams for fitting hearing aids, which can be prohibitively expensive for many older adults. Hearing Loss and Healthy Aging is the summary of a workshop convened by the Forum on Aging, Disability, and Independence in January 2014 on age-related hearing loss. Researchers, advocates, policy makers, entrepreneurs, regulators, and others discussed this pressing social and public health issue. This report examines the ways in which age-related hearing loss affects healthy aging, and how the spectrum of public and private stakeholders can work together to address hearing loss in older adults as a public health issue"--Publisher's description.